PSYCHOANALYSIS OF THE MAIN CHARACTER IN RAINBOW ROWELL’S FANGIRL - Novita Adelia Harahap; Ayu Melati Ningsih (Fakultas Sastra UMN AL Washliyah, 2022)
The main objectives of this research are to find: 1) what are the personality of the main character in Freud's Psychoanalysis? and 2) what kind of conflicts are experienced by the main character. This study used descriptive qualitative method. This thesis discusses psychoanalysis developed by Sigmund Freud: id, ego and superego. This thesis also discusses the conflicts experienced by the main character: internal conflicts (related to the psychology of the main character) and external conflicts (related to other characters, society, nature or things outside of her).